2015
DOI: 10.1111/nph.13286
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional networks in plant immunity

Abstract: 932I.932II.933III.934IV.938V.941943References943 Summary Next to numerous abiotic stresses, plants are constantly exposed to a variety of pathogens within their environment. Thus, their ability to survive and prosper during the course of evolution was strongly dependent on adapting efficient strategies to perceive and to respond to such potential threats. It is therefore not surprising that modern plants have a highly sophisticated immune repertoire consisting of diverse signal perception and intracellular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
346
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(359 citation statements)
references
References 192 publications
10
346
1
2
Order By: Relevance
“…Activation of PTI involves massive transcriptional reprogramming to mount defense responses against invading pathogens (Bigeard et al, 2015;Tsuda and Somssich, 2015;Garner et al, 2016;Birkenbihl et al, 2017a). General PTI responses include reinforcement of cell wall through deposition of callose and production of defense-related proteins (Boller and Felix, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of PTI involves massive transcriptional reprogramming to mount defense responses against invading pathogens (Bigeard et al, 2015;Tsuda and Somssich, 2015;Garner et al, 2016;Birkenbihl et al, 2017a). General PTI responses include reinforcement of cell wall through deposition of callose and production of defense-related proteins (Boller and Felix, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Effectors can be recognized by specific resistance proteins, leading to a so-called effector-triggered immunity (ETI) or gene-for-gene resistance (Craig et al 2009;Jones and Dangl 2006). The combined effect of such mechanisms, called nonhost resistance, can block efficiently the invasion of genetic variants of nonadapted pathogens, both locally at the infection site and systemically in uninfected leaves (Craig et al 2009;Tsuda and Somssich 2015). Remarkably, since nonhost resistance is typically both broad-spectrum and durable, it has considerable value for crop improvement .…”
mentioning
confidence: 99%
“…Between 5 to 30 min after activation of PRRs, ethylene (ET) accumulation, endocytosis of PRRs, and transcriptional reprograming of early response genes (ERGs) are observed that lead to the amplification of the immune responses (Robatzek et al 2006;Spanu et al 1994;Tsuda and Somssich 2015;Tullai et al 2007). Additionally, programmed cell death or hypersensitive response has been described as part of the immune response and is regulated by the ROS accumulated during the plantpathogen interactions (Bellin et al 2013;Lehmann et al 2015).…”
mentioning
confidence: 99%
“…In response to developmental or environmental cues, JA-Ile concentration rises, which promotes the interaction between COI1 and JAZs and subsequent degradation of JAZ repressors through the 26S proteasome (10,21). Activation of MYC and other JAZ-interacting transcription factors leads to transcriptional reprograming and results in a plethora of JA-mediated physiological responses (22)(23)(24).…”
mentioning
confidence: 99%
“…Although activation of the JA signal transduction pathway is essential for plant resistance to chewing insects and necrotrophic pathogens, it also leads to inhibition of SA signaling through hardwired molecular cross-talk between the two pathways (1,22,(25)(26)(27). Because the SA signaling pathway is critical for plant defense against biotrophic and hemibiotrophic pathogens, activation of JA signaling makes plants vulnerable to biotrophic and hemibiotrophic pathogens.…”
mentioning
confidence: 99%